Edith Stein's itinerary: phenomenology, Christian philosophy, and Carmelite spirituality = Edith Steins intellektueller Weg : Phänomenologie, christliche Philosophie und karmelitische Spiritualität - Klueting, Harm; Klueting, Edeltraud (Schriften des Forschungsinstituts der Deutschen Provinz der Karmeliten, 2021)
"In August 2019, the fifth international congress of the 'International Association for the Study of the Philosophy of Edith Stein' (IASPES) took place at the University of Cologne. Of the 57 papers presented at this prominent conference prepared and chaired by the historian and theologian Harm Klueting, 54 were accepted for publication in revised versions. Professor Klueting was able to add three other contributions -- among them by the director of the Research Institute of the German Province of the Carmelites at Bamberg, the historian and theologian Edeltraud Klueting, who acts as co-editor. The congress volume, published only a little more than a year after the congress despite significant constraints due to the Corona pandemic, contains 29 contributions in English, 21 in German, and seven in Spanish or French on the subjects 'Biographical questions', 'Edith Stein and thinkers of the past', 'Edith Stein and other contemporary thinkers', 'Anthropology -- Women and men', 'Philosophy -- phenomenology and Christian philosophy', 'Society and politics', 'Theology and spirituality', and 'Experiences with Edith Stein'."--